Association between atmospheric ozone levels and damage to human nasal mucosa in Florence, Italy - Pacini, Stefania; Giovannelli, Lisa; Gulisano, Massimo; Peruzzi, Benedetta; Polli, Gianni; Boddi, Vieri; Ruggiero, Marco; Bozzo, Corrado; Stomeo, Francesco; Fenu, Grazia; Pezzatini, Silvia; Pitozzi, Vanessa; et al. (Environmental and molecular mutagenesis, 2003)
We evaluated the effects of urban air pollutants on human nasal mucosa over an 8‐month period on 102 subjects living in Florence, Tuscany, Italy. A group of subjects living in a city with a lower level of pollution (Sassari, Sardinia, Italy) was also analyzed. Nasal mucosa cells were harvested by brushing, a noninvasive procedure. Half of the cells were used for genotoxicity studies using the alkaline comet assay, and half for morphological studies. The levels of DNA damage in the nasal mucosa were considerably higher (+73%) in the subjects living in Florence than in Sassari. High levels of atmospheric ozone in Florence air correlated with DNA damage, and to the prevalence of inflammatory pathologies of the upper respiratory tract, although the ozone concentrations were below the Italian recommended attention level. Furthermore, higher levels of DNA damage were correlated with a dysfunction in the ability to maintain a normal epithelial cell structure. These data suggest an association between ozone air levels and damage in the upper respiratory tract. It remains unclear whether ozone itself or other associated pollutants are responsible for the observed alterations. Environ. Mol. Mutagen. 42:127–135, 2003. © 2003 Wiley‐Liss, Inc.